The DC Choice Incentive Act of 2003: A Historic Moment for Children - Davis, O.S.F.S., William F.; Pearsall, Christopher S. (Catholic Education: A Journal of Inquiry and Practice, 2004)
Voucher programs have long endured intense legislative challenge and judicial scrutiny. This article details the recent history of a successful voucher implementation plan for the District of Columbia. The importance of a broad base of politically active and astute citizens, parents, religious leaders, and Federal legislators is highlighted. The success of the voucher program detailed here may serve as a model for other programs.